Perancangan Instalasi Penerangan Pada Gedung Laboratorium Dan Perkuliahan Terpadu Universitas Borneo Tarakan - Aprizulkifli Aprizulkifli; Sugeng Riyanto (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Borneo Tarakan, 2021)
The design of the lighting installation in the Integrated Lecture and Laboratory Building of the University of Borneo Tarakan. Generates a total power of about 31,048 KW with MCCB capacity on the main panel of 150 A. In this building is divided into 3 floors (1, 2 and Top Floor). Each group has its respective power (18,400, 12,328 and 320 Watt) and the nominal currents of each group are (35, 35, and 2 Ampere). The resulting stress loss is 0.4%